Repair of osteochondral defect using icariin-conditioned serum combined with chitosan in rabbit knees - Juntao Zhang; Dong Ming; Qiang Ji; Aifeng Liu; Chao Zhang; Jianjie Jiao; Man Shang (BMC, 2020)
Abstract Background Osteochondral defects caused by an acute traumatic injury or articular degeneration remains difficult to be manipulated. Repair of articular defects is still a great challenge for both tissue engineers and orthopedic surgeons. Therefore, combination of biomaterials with cartilage promotive drugs is well worth being developed to support the regeneration of both cartilage and subchondral bone. Methods Rabbits undergoing osteochondral defect surgery were intrarticularly injected with icariin-conditioned serum (ICS), chitosan (CSSH) and combination of ICS with CSSH, respectively. Gait analysis was performed using VICON motion capture system. ICRS score and immunohistochemical (IHC) analysis including H&E, Safranin O, toluidine blue and collagen II staining was employed to evaluate macroscopic cartilage regeneration and determine the morphologic repair of cartilage. Results Rabbits with the treatment of ICS or CSSH alone showed mild improvement in hopping time and range of joint angles while ICS-CSSH group exhibited longer jumping time and larger range of joint angles. In addition, femoral condyle in ICS-CSSH rabbits could be seen with more native cartilage and subchondral bone regeneration in both macroscopic observation and IHC analysis. Conclusion ICS combined with CSSH could promote the repair of osteochondral defect in rabbit knees. Combination of biomaterials with cartilage promotive drugs may ultimately have profound implications in the management of cartilage defect.